Always something else : urban Asia and Africa as experiment - Simone, A. M. (Abdou Maliqalim) (Carl Schlettwein lectures ;, 2016)
The most extensive urban demographic transitions ahead will take place in Africa and Asia. These transitions occur in regions where the majority of inhabitants remain trapped in vulnerable employment, which limits the capacities to plan, save, invest, and afford critical amenities, as well as limits the horizons of what is considered possible. Yet, the aspirations for mobility, security, consumption, and attainment are enormous. How can different rationalities and practices of everyday sociality be more effectively connected to the prevailing concepts informing formal political and policymaking projects? How can incommensurable facets of urban life be folded into each other as a matter of an enlarged political practice? There is no pre-existent map that tells us how to link these equally important dimensions of urban life. Thus, any effort to consider the relationship between them is by necessity an experiment.